Influence of Functionally Obsolete Bridges on the Efficiency of Road Network. Part II: Case Studies - Zenonas Kamaitis (The Baltic Journal of Road and Bridge Engineering)
This study is the first practical step in Lithuania to identify the characteristics causing the bridges to be functionally obsolete. A bridge of which current deck geometric characteristics, safety barriers or railings, underclearances, and roadway approach alignment are deficient and not consistent with current design standards (or traffic demands) can be considered as functionally obsolete. In Part I of this paper the criteria of functionally obsolete bridges, deficiency categories and assessment of deficient structures are presented. The Part II reports experience in city bridge stock of 83 structures for a short period of 2–5 years on this subject. Surveying revealed that 58.5% of bridge stock shows minor or obvious signs of functional aging. Evaluation and rating of city bridge stock was undertaken. Illustrative examples of functionally obsolete bridges are presented. Recommendations for improvement of the geometrical characteristics of bridges in existing Lithuanian design codes are envisaged.